Pharmacogenetics-guided dalcetrapib therapy after an acute coronary syndrome: the dal-GenE trial . (20th July 2022) - Tardif, Jean Claude; Pfeffer, Marc A; Kouz, Simon; Koenig, Wolfgang; Maggioni, Aldo P; McMurray, John J V; Mooser, Vincent; Waters, David D; Grégoire, Jean C; L'Allier, Philippe L; Wouter Jukema, J; White, Harvey D.; et al.
Abstract: Aims: In a retrospective analysis of dal-Outcomes, the effect of dalcetrapib on cardiovascular events was influenced by an adenylate cyclase type 9 ( ADCY9 ) gene polymorphism. The dal-GenE study was conducted to test this pharmacogenetic hypothesis. Methods and results: dal-GenE was a double-blind trial in patients with an acute coronary syndrome within 1–3 months and the AA genotype at variant rs1967309 in the ADCY9 gene. A total of 6147 patients were randomly assigned to receive dalcetrapib 600 mg or placebo daily. The primary endpoint was the time from randomization to first occurrence of cardiovascular death, resuscitated cardiac arrest, non-fatal myocardial infarction, or non-fatal stroke. After a median follow-up of 39.9 months, the primary endpoint occurred in 292 (9.5%) of 3071 patients in the dalcetrapib group and 327 (10.6%) of 3076 patients in the placebo group [hazard ratio 0.88; 95% confidence interval (CI) 0.75–1.03; P = 0.12]. The hazard ratios for the components of the primary endpoint were 0.79 (95% CI 0.65–0.96) for myocardial infarction, 0.92 (95% CI 0.64–1.33) for stroke, 1.21 (95% CI 0.91–1.60) for death from cardiovascular causes, and 2.33 (95% CI 0.60–9.02) for resuscitated cardiac arrest. In a pre-specified on-treatment sensitivity analysis, the primary endpoint event rate was 7.8% (236/3015) in the dalcetrapib group and 9.3% (282/3031) in the placebo group (hazard ratio 0.83; 95% CI 0.70–0.98). Conclusion: Dalcetrapib did not significantly reduce the risk of occurrence of the primary endpoint of ischaemic cardiovascular events at end of study. A new trial would be needed to test the pharmacogenetic hypothesis that dalcetrapib improves the prognosis of patients with the AA genotype. Clinical Trial Registration: Trial registration dal-GenE ClinicalTrials.gov Identifier: NCT02525939 Structured Graphical Abstract: Structured Graphical Abstract Dalcetrapib in patients with AA genotype at variant rs1967309 in the ADCY9 gene. CI, confidence interval; CV, cardiovascular; HR, hazard ratio.